Could There be a Good Side to COVID-19 Pandemic? - Donna Shaw; Theressa Brahim; Catherina Chang Martinez (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2021)
As the COVID-19 pandemic unfolded, resulting in loss of lives, burnout, anxiety, and depression related to social distancing and quarantine measures, some positive changes have been reported at the individual, interpersonal, and community level. Self-reflection, social connectedness, connectivity, innovation, and resilience have emerged as positive values that have contributed to decrease in burnout during the post-COVID pandemic era.